2021
DOI: 10.1001/jama.2021.15072
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Adverse Events After COVID-19 mRNA Vaccination

Abstract: IMPORTANCE Safety surveillance of vaccines against COVID-19 is critical to ensure safety, maintain trust, and inform policy.OBJECTIVES To monitor 23 serious outcomes weekly, using comprehensive health records on a diverse population. DESIGN, SETTING, AND PARTICIPANTSThis study represents an interim analysis of safety surveillance data from Vaccine Safety Datalink. The 10 162 227 vaccine-eligible members of 8 participating US health plans were monitored with administrative data updated weekly and supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
502
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(592 citation statements)
references
References 31 publications
46
502
3
3
Order By: Relevance
“…The observed rate of 0.8 per million doses for both vaccines in this cohort was not higher than expected background rate. This is in keeping with our analysis, which also did not demonstrate an increased rate of ITP following Pfizer-BioNTech vaccination, as well as other studies which have reported similar findings relating to mRNA COVID-19 vaccines [9] , [10] , [11] , [13] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The observed rate of 0.8 per million doses for both vaccines in this cohort was not higher than expected background rate. This is in keeping with our analysis, which also did not demonstrate an increased rate of ITP following Pfizer-BioNTech vaccination, as well as other studies which have reported similar findings relating to mRNA COVID-19 vaccines [9] , [10] , [11] , [13] .…”
Section: Discussionsupporting
confidence: 93%
“…Emerging evidence suggests a causal link between ITP and COVID-19 vaccines, particularly AstraZeneca vaccine [9] , [10] . Other studies have investigated ITP following mRNA vaccines and to date found no association [11] , [12] , [13] . In our analysis, we examine a series of reported cases of ITP following vaccination with AstraZeneca and Pfizer-BioNTech vaccines and compare these to expected background rates in Victoria, Australia.…”
Section: Introductionmentioning
confidence: 95%
“…However, an association between both mRNA vaccines and myocarditis/pericarditis was noticed in younger individuals aged 12–39 years, which requires further investigation (Fig. 4 ) 113 .
Fig.
…”
Section: Introductionmentioning
confidence: 94%
“…Hypersensitivity reaction to vaccine components or anaphylactic reaction at the first administration are the only contraindications to vaccine administration. The latter is an exceptional reaction, and it can be treated with subcutaneous administration of adrenaline; no case of death due to anaphylaxis have been reported so far [9].…”
Section: Sars-cov-2 Vaccines Approved By Ema and Aifamentioning
confidence: 99%